Project Report on Intelligent Traffic Mangement System Using Lab VIEW - REJIN M A, SIDDARAMESHWAR A, SOUMTH S and SOMASHEKHAR M (2011)
INTERNAL GUIDE : Kavitha D EXTERNAL GUIDE : Nallusamy V USN NO : 1MJ08EC073, 1MJ08EC088, 1MJ08EC090 and 1MJ09EC414 CARRIED OUT AT : Mvj Coolege Of Engineerig Channasandra Near ITPB Bangalore-560 067 ACC NO : PR1875
Keywords: Intelligent Traffic Mangement System